Awareness of corporate social responsibility among selected companies in Malaysia: an exploratory note / Nik Nazli Nik Ahmad and Norliana Akida Abdul Rahim - Nik Ahmad, Nik Nazli (Accounting Research Institute (ARI) & Faculty of Accountancy, 2005)
The purpose of this paper is three-fold. First, to explore whether companies in Malaysia are aware of corporate social responsibility (CSR). Second, to explore managers’ awareness of CSR, and third, to explore the managers’ perceptions of the extent to which CSR initiatives are being implemented by companies in Malaysia. The study was carried out with managers from a sample of public-listed companies in Malaysia. The primary insight is that the companies and managers generally have some understanding of the concept of CSR. However, though some companies have implemented certain CSR initiatives, the number is still low. A substantial percentage of the respondents feel that while these initiatives are considered to be important by their respective companies, no implementation is being planned. One major area for future research is to investigate the reasons why very few companies in Malaysia are implementing CSR initiatives despite the survey suggesting that companies have some awareness of the concept of CSR.